FRI0108 Time to first treatment is associated with a refractory course of rheumatoid arthritis. (15th June 2017) - Bécède, M; Alasti, F; Haupt, L; Kerschbaumer, A; Landesmann, U; Supp, G; Smolen, J; Aletaha, D
Abstract : Background: It is an ongoing matter of research, whether the natural course of rheumatoid arthritis (RA) can be altered by an early intervention, a concept historically referred to as the "window of opportunity" (1). So far, only short-term disease activity outcomes have been investigated (e.g. "remission off drugs"), which are, however, inherently affected by the unknown rate of underlying rate self-limiting disease. It is unclear, whether among those, who eventually develop RA, the disease course is really affected by the timing of their initial treatment. Objectives: To explore whether the long-term course of RA is different according to the delay of initial treatment. Methods: Based on a longitudinal observational dataset, we initially identified a group of patients with an observed refractory disease, we defined presenting with ongoing moderate or high disease activity (by the Simplified Disease Activity Index, SDAI), despite at least three courses of DMARDs, of which at least on course was a biological compound. To ensure that sufficient time had been allowed for the previous treatments to be exert their non-effects, we also required these patients to have total treatment time of at least 18 months in accordance with treat to target strategy (3 x 6 months). We identified 399 patients with a treatment time of at least 18 months. 48 patients were excluded despite fulfilling the disease activity criteria, because they haven't experienced enough treatment courses, or had received a biological compound yet, to claim refractory disease as per our criteria above. We could include 69 refractory and 282 non-refractory patients in our analyses and then performed logistic regression analysis to assess the effects of different characteristics at baseline, including disease duration, on becoming refractory. Results: By comparing patient characteristics (Table 1 ), more of the patients, who later will become refractory, are female (94.2% Vs 73.4%, p>0.001), have higher baseline disease activity (SDAI of 25.5 vs 17.7, p<0.001), and longer delay of the initial treatment from symptom onset (3.17 Vs 1.34 years, p=0.001). The multivariable logistic regression model confirmed that a longer delay of first treatment is independently afflicted with a higher probability of a refractory disease course at a later stage. This model was adjusted for disease activity at baseline and gender (p<0.001, Figure 1 ). With increasing treatment delay, the chance of a dire disease course rises by approximately 1% every 6 months. Conclusions: Our data suggest that delay to initial treatment in RA affects the long-term course of RA. Earlier treatment initiation thus may change the severity of RA. References: van Nies, J.A., et al., What is the evidence for the presence of a therapeutic window of opportunity in rheumatoid arthritis? A systematic literature review. Ann Rheum Dis, 2014. 73(5): p. 861–70. Disclosure of Interest: None declared